High-resolution visualization of pial surface vessels by flattened whole mount staining - Xu, Yanying; Zhang, Jiasheng; Lee, Heon-Woo; Zhang, Guogang; Bai, Yongping; Simons, Michael (iScience, 2023)
Understanding development of the cerebral vasculature is essential for the central nervous system (CNS) research and therapeutic developments. Here, we developed a simple, convenient, and fast method—the flattened cortex whole mount (FCWM) technique—for imaging of pial cerebral vessels. FCWM involves dissection of the whole cerebral cortex followed by flattening, sectioning and application of CLARITY technology. Compared to conventional methods, FCWM offers several advantages including (1) high-resolution visualization of the whole cortex pial surface vessel structures and distributions; (2) precise localization of a particular blood vessel, allowing observations of a desired blood vessel during normal development or in disease settings; (3) compatibility with confocal imaging. Application of FCWM for examination of cerebral vasculature during postnatal development or in stroke settings allowed us to demonstrate that cerebral blood vessels manifest type-specific maturation and remodeling which are linked to the rate of endothelial proliferation. [Display omitted] •High resolution imaging of pial cortex vessel in a 2D view•Compatibility of processed cortex tissue with confocal imaging•Precise localization of pial surface vessels with high magnification imaging Vascular anatomy; Medical imaging; Neuroscience